The Role of Russian Writers and Intellectuals in the 1905 Revolution in Russia - Hadi, Iman Jawad; Hadi, Ali Hussien (Dirasat: Human and Social Sciences, 2025)
Objectives: The main objective of this study is to examine the crucial role that Russian writers and intellectuals played in catalyzing the 1905 Revolution in Russia. Specifically, the study sought to analyze how their literary works, philosophical ideas, and political writings challenged Tsarist autocracy, depicted the suffering of the masses, and inspired opposition movements. The study aimed to highlight the defiant writings that contributed to the rise of political figures and the eventual overthrow of the repressive regime. Methods: The historical narrative and analytical methods were employed, conducting a comparative analysis of prominent works by renowned authors such as Tolstoy, Gorky, and Chekhov. This analysis focused on their depiction of social discontent, class struggles, and the decline of the aristocratic system. Results: The findings revealed that the writings of Russian intellectuals played a pivotal role in spreading revolutionary ideas, challenging autocracy, and inspiring opposition movements. Their literary works, philosophical discussions, and political pamphlets resonated with the discontented masses, fostering a spirit of resistance against the oppressive Tsarist regime. The study highlighted Anton Chekhov's play "The Cherry Orchard," which symbolically reflected the aristocracy's resistance to change through its rich symbolism and detailed character portrayals. Conclusions: Although the Tsarist regime was not overthrown, the 1905 Revolution paved the way for subsequent transformations. The study concluded that the writings of Russian intellectuals awakened political consciousness and laid the groundwork for the 1917 Revolution. Their literary contributions expanded the rhetorical space, facilitating societal change. The study emphasized the immense power of the written word in the struggle against Tsarist tyranny.